(untitled) (Research, Society and Development, 2022)
Solar radiation is essential for several biological processes, it acts directly in the stimulation of melanocytes and as a precursor of vitamin D. However, according to the degree of exposure, there are several damages that can be caused, such as burns, photoaging and skin cancer. . In this way, the search for products of phytochemical origin, have great potential for the discovery of plants with photoprotective activity, and can be incorporated into cosmetic formulations increasing their effectiveness. Given the above, the objective of this work was to identify the phytochemical compounds, extracts and plant fractions that present photoprotective activity evidenced by in vitro and/or in vivo tests proven in the literature. It was a study that was developed through an integrative literature review between the years 2011 and 2021, in order to answer the following guiding question: “Which phytochemical compounds have photoprotective activity?” Plant extracts are the most used compounds in research, most studies aim to highlight the value of the Sun Protection Factor (SPF). On the other hand, isolated compounds and fractions are more associated with synergism when incorporated into photoprotective products. In view of this, the association of these compounds with synthetic sunscreens may require less toxicity, since these synthetic molecules can cause many side effects, and in addition to hindering users’ adherence, they can compromise the healthy appearance of the skin. Therefore, the use of phytochemicals appears as a promising alternative in the development of sustainable, effective and safe sun protection formulations.